Nursing process applied to post-operated user of exploratory laparotomy - Rojas-Vega, María Emma (Universidad de Sonora, 2019)
Introduction: the present case study exposes a post-operative exploratory laparotomy user, hospitalized at the Intensive Care Unit service in the city of Hermosillo, Sonora, Mexico. Objective: exhibit the structure that allowed covering the individual needs of the user in question. Methodology: a focused nursing assessment was carried out according to M. Gordon´s Nursing Assessment Guide of functional patterns typology for an adult person. Likewise, Nursing Diagnoses were used: Definitions and Classification for the selection of nursing diagnoses, as well as the Nursing Results Classification and Nursing Interventions Classification for the planning of interventions and activities. Information was also retrieved from the clinical file of the hospital unit. Results: a total of 10 nursing diagnoses were identified, of which four are real diagnoses and the rest are risk diagnoses. Conclusions: it is vital that the nursing staff implements all their knowledge and skills in the application of their interventions during each stage of the NP, by this way it will be possible to provide a quality and completely fundamental nursing care.